Sons and descendant s a social history of kin groups and family names in the early neo-Babylonian period, 747-626 B.C. - Nielsen, John P. 1973- (Culture and History of the Ancient Near East, 2011)
Sons and Descendants represents the first comprehensive study of Babylonian family names. Drawing primarily on evidence from legal documents from the early Neo-Babylonian period (747-626 B.C.), the book examines the presence of large, named kin groups at the major Babylonia cities, considering their origins and the important roles their members played as local elites in city governance and temple administration. The period of Neo-Assyrian ascendance over Babylonia marks the first for which there is adequate textual material to allow for a study of these groups, but their continued presence and prominence in Babylonia under the native Neo-Babylonian dynasty and the Persian Empire means that this work is an important contribution to Assyriological understanding of Neo-Babylonian society.